The Influence of Education, Social, and Healthcare Expenditures on the Human Development Index (HDI) in Bireuen Regency: English - Alda, Rizki; Nasution, Zulkifli; Lubis, Satia Negara; Lubis, Arga Abdi Rafiud Darajat (CV. ARGA FARMA, 2024)
This study investigates r the effects of education r, social r, and healthcare expenditures on the Human Development Index (HDI) in Bireuen Regency r. Using quantitative analysis and regression methods, data from official government sources were analyzed to explore the relationships between these variables. The results indicate that education spending has a significant negative effect on HDI, highlighting the need for better allocation and use of resources within the education sector. Conversely, social expenditure showed no significant positive effect on HDI r, pointing to the need for improvements in social programs and policies. In contrast, healthcare spending had a significant positive impact on HDI, underscoring the importance of sufficient healthcare resource allocation. Collectively, these expenditures had a significant positive effect on HDI, emphasizing the necessity of a comprehensive approach to budget allocation. The study recommends optimizing education funding to prioritize quality improvements and enhancing the effectiveness of social spending programs to better meet the needs of the population. Adequate funding for healthcare is essential to improving human development outcomes.